Analisis Perubahan Perilaku Konsumen E-Commerce Pada Masa Pandemi Covid-19 (Studi pada konsumen Shopee di Kota Sukabumi) - Salsa Dewi Nurfadilah (International Journal Administration, Business & Organization, 2021)
This research aims to determine and obtain data as well as information about the factor that influence changes in Shopee consumer behavior during the Covid-19 pandemic. This research was conducted in Sukabumi City with the number of respondents as many as 114 people. The data collection method used a questionnaire and analyzed with factor analysis using SPSS. The technique of testing the data from the questionnaire results in this research is the validity test using correlation, reliability testing using Cronbach alpha, and using factor analysis to find new factors that influence changes in consumer behavior. The results showed that changes in consumer behavior can be influenced by 4 factors, namely: lifestyle factors, motivation factors, social factors, and learning factors. A person's lifestyle supported by motivational factors can have an influence in making consumer decisions to make purchases, so consumer behavior can change over time supported by 2 other factors, namely, social factors and learning/experience.